Mengidentifikasi Jenis Tanah, Batas Plastis, Batas Cair Tanah Lempung - Sheila Ananda Putri Pertiwi; Agata Iwan Candra; Tiara Sherlyta Sari; Annas Dwi Safi'i; Zaizafun Zakiya (Jurnal Talenta Sipil, 2023)
Soil is a material consisting of mineral grains bonded to one another. Soil itself has various types. One of them is clay. Clay soil is microscopic soil particles that come from weathering rocks. The water content in clay tends to be high so it has a low bearing capacity. In addition, it also has a high shrinkage. Therefore, the management of clay soils must be handled properly. The method used is Gradation Sieve, Liquid Limit, and Plastic Limit. These three methods are considered suitable for conducting tests on clay samples. From these tests, obtained D10 values of 0.14, D30 of 0.5 and D60 of 1.6. And the results of the calculation of Cu and Cc obtained the values of Cu 4 and 1 Cc 3 so that the soil is classified into the GC group (well granded gravel with clay). For the results of the liquid limit test (LL) on the soil samples that have been studied, the average liquid limit value of 25 strokes is 41.12%. For the results of the plastic limit (PL) test on the soil sample, the plastic limit value of 32.42% was obtained. And the results of reducing the liquid limit with the plastic limit obtained a plastic index value of 8.70% so that the soil is included in the criteria for low plasticity index.